The Legal Fremwork and practice of Using Intellectual Property Right as Fiduciary Collateral in Indonesia : Challengs and Solution - Fahmi Ihsan Margolang; Fenny Fenny (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This paper examines the legal framework and practical implementation of using Intellectual Property Rights (IPRs) as fiduciary collateral in Indonesia. The study identifies existing legal uncertainties and administrative challenges that hinder the optimization of IPRs as collateral objects, such as the absence of technical implementation regulations and limited awareness among stakeholders. Through normative legal analysis supported by empirical evidence, this research explores how the current fiduciary security law can be adapted to better accommodate IPRs, highlighting the potential for IPRs to enhance access to finance, particularly for creative economy actors. The paper also presents solutions, including the need for clear implementing regulations, capacity-building among stakeholders, and stronger coordination among government institutions. Ultimately, the research emphasizes the strategic importance of integrating IPRs into financial mechanisms and proposes actionable steps for regulatory and institutional reform.